Synthesis of Ni(ii)–Mn(ii) complexes using a new mononuclear Ni(ii) complex of an unsymmetrical N2O3 donor ligand: structures, magnetic properties and catalytic oxidase activity. Issue 13 (17th March 2021) - Maity, Souvik; Mahapatra, Prithwish; Ghosh, Tanmoy Kumar; Gomila, Rosa M.; Frontera, Antonio; Ghosh, Ashutosh
Abstract : Three new Ni II –Mn II complexes have been synthesized by employing a new Ni(ii ) complex of an unsymmetrical N2 O3 donor ligand; one of which containing azide co-anions readily oxidizes 3, 5-DTBC to 3, 5-DTBQ. Abstract : A new Ni(ii ) complex [NiL] (complex 1 ) of an asymmetrically di-condensed N2 O3 donor Schiff base ligand, N -salicylidene- N ′-3-methoxysalicylidene-1, 3-propanediamine (H2 L), has been synthesized and utilized for the synthesis of three heterometallic complexes, [(NiL)2 Mn(NCS)2 (CH3 OH)2 ]·CH3 OH (2 ) [(NiL)2 Mn(N(CN)2 )2 (CH3 OH)2 ]·CH3 OH (3 ) and [(NiL)2 Mn2 (N3 )2 (μ1, 1 -N3 )2 (CH3 OH)2 ] (4 ). Single crystal X-ray diffraction analyses show that complexes 2 and 3 have linear trinuclear structures where two tridentate O3 donor (NiL) units are coordinated to the central octahedral Mn(ii ) centre, whereas complex 4 has a centrosymmetric tetranuclear structure where two binuclear (NiL)Mn units are linked via two phenoxido and two μ1, 1 -N3 bridges. Among the heterometallic complexes (2–4 ), only 4 is active towards the catalytic oxidation of 3, 5-di- tert -butylcatechol to the corresponding quinone. The turnover number for the aerobic oxidation of 3, 5-DTBC is 935 h −1 . ESI-mass spectra have been recorded to scrutinize the mechanistic pathway of this catalytic reaction. Variable temperature magnetic susceptibility measurements suggest that complexes 2–4 are antiferromagnetically coupled with coupling constants ( J ) of −4.84 and −5.23 cm −1 for complexes 2 and 3, respectively and J 1 = −2.20 cm −1, J 2 = 1.13 cm −1 and J 3 = −1.12 cm −1 for complex 4 . DFT calculations have been used to rationalize the magnetic super-exchange in complexes 2–4, by computing the theoretical coupling constants and analyzing the spin density plots.